Square-pyramidal iron coordination modules as potential spin switches for the chemisorption on gold - Kaempf, Holger; Daunke, Daniel; Heinemann, Frank Wilhelm; Grohmann, Andreas (Applied Physics A-Materials Science & Processing, 2008)
Octahedral iron(II) complexes of a unique pyridine-derived tetrapodal pentadentate polyamine ligand, 2,6-C5H3N(CMe[CH2NH2](2))(2), show temperature-dependent spin crossover (SCO) depending on the nature of a sixth monodentate ligand L (imidazol or pyridine derivative). For L=1-methylimidazol, the redox behaviour of the complex, as determined by cyclic voltammetry, suggests an accompanying ligand exchange. Pyridine-4-thiol and the disulphides: 4-(2-methyldisulphanyl)pyridine, 4-(2-hexadecyldisulphanyl)pyridine and 1,2-bis([pyridine-4-yl]methyl)disulphane, were studied as mono-dentate ligands L, with a view to enable chemisorption of iron(II) complexes on a gold surface. In the case of pyridine-4-thiol, the participation of the thiolate functional group in iron coordination is difficult to suppress, whereas the disulphides enter into yet unrecorded redox chemistry with iron(II), yielding a di-iron(III) complex containing a persulphide bridge (S-2(2-)).